Characterization of a Bacillus velezensis strain isolated from Bolbostemmatis Rhizoma displaying strong antagonistic activities against a variety of rice pathogens - Zhou, Jianping; Xie, Yunqiao; Liao, Yuhong; Li, Xinyang; Li, Yiming; Li, Shuping; Ma, Xiuguo; Lei, Shimin; Lin, Fei; Jiang, Wei; He, Yong-Qiang (Frontiers in Microbiology, 2022)
Biological control is an effective measure in the green control of rice diseases. To search for biocontrol agents with broad-spectrum and high efficiency against rice diseases, in this study, a strain of antagonistic bacterium BR-01 with strong inhibitory effect against various rice diseases was isolated from Bolbostemmatis Rhizoma by plate confrontation method. The strain was identified as Bacillus velezensis by morphological observation, physiological and biochemical identification, and molecular characterization by 16S rDNA and gyrB gene sequencing analysis. The confrontation test (dual culture) and Oxford cup assays demonstrated that B. velezensis BR-01 had strong antagonistic effects on Magnaporthe oryzae, Ustilaginoidea virens, Fusarium fujikuroi, Xanthomonas oryzae pv. Oryzicola, and Xanthomonas oryzae pv. oryzae, the major rice pathogens. The genes encoding antimicrobial peptides (ituA, ituD, bmyB, bmyC, srfAA, fenB, fenD, bacA, and bacD) were found in B. velezensis BR-01 by PCR amplification with specific primers. B. velezensis BR-01 could produce protease, cellulase, β-1,3-glucanase, chitinase, indoleacetic acid, siderophore, and 1-aminocyclopropane-1-carboxylate (ACC) deaminase, and might produce three lipopeptide antibiotics, surfactin, iturin, and fengycin based on Liquid chromatography–mass spectrometry (LC-MS) results. Furthermore, the plant assays showed that B. velezensis BR-01 had significant control effects on rice bacterial blight and bacterial leaf streak by pot experiments in greenhouse. In conclusion, B. velezensis BR-01 is a broad-spectrum antagonistic bacterium and has the potential as the ideal biocontrol agent in controlling multiple rice diseases with high efficiency.